2013
DOI: 10.1371/journal.pone.0064355
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Bias Modification versus CBT in Reducing Adolescent Social Anxiety: A Randomized Controlled Trial

Abstract: Social anxiety is a common mental disorder among adolescents and is associated with detrimental long term outcomes. Therefore, this study investigated the efficacy of two possible early interventions for adolescent social anxiety and test anxiety. An internet-based cognitive bias modification (CBM; n = 86) was compared to a school-based cognitive behavioral group training (CBT; n = 84) and a control group (n = 70) in reducing symptoms of social and test anxiety in high socially and/or test anxious adolescents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
97
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(98 citation statements)
references
References 40 publications
1
97
0
Order By: Relevance
“…., but equally they do not tend to deteriorate rapidly'. 93 More recent data provided in Sportel et al 94 (table 3) Test Anxiety Inventory 95 ), the effect had not entirely waned at 12-month follow-up. This may be generalisable to other forms of successful psychological therapy, and conservatively we elected to assume that all benefit had dissipated at 52 weeks post treatment, although a longer period of 104 weeks was used in sensitivity analyses.…”
Section: Results Of the Economic Systematic Reviewmentioning
confidence: 89%
“…., but equally they do not tend to deteriorate rapidly'. 93 More recent data provided in Sportel et al 94 (table 3) Test Anxiety Inventory 95 ), the effect had not entirely waned at 12-month follow-up. This may be generalisable to other forms of successful psychological therapy, and conservatively we elected to assume that all benefit had dissipated at 52 weeks post treatment, although a longer period of 104 weeks was used in sensitivity analyses.…”
Section: Results Of the Economic Systematic Reviewmentioning
confidence: 89%
“…The same concerns the study by Spence et al [12], they reported that 29% dropped out in a generic CBT condition, 21% in CBT specifically tailored to SAD, and 10% in a WL condition. However, Sportel et al [13] found comparable or even higher dropout rates: 32% in the CBT group, who did not receive the allocated intervention, compared to 65% in the internet-based cognitive bias modification group, and 17% in the control group. Higher dropout rates were reported by Ingul et al [11].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, 2 recently conducted RCT also demonstrated the efficacy of internet-delivered CBT interventions in these patients [12, 13]. …”
Section: Introductionmentioning
confidence: 99%
“…These initially disappointing results could be due to only single training sessions being administered. Interestingly, a recent study looking specifically at adolescents with high levels of social concerns showed that a combination of CBM-A and CBM-I was effective (Sportel et al, 2013), but these effects were less persistent than those of other frontline treatments such as CBT. One strategy to improve effectiveness may be to increase userengagement of these computerized training programs.…”
Section: Age-appropriate Sad Interventions To Capitalize On Plasticitymentioning
confidence: 99%